First world petro-politics : the political ecology and governance of Alberta - Adkin, Laurie Elizabeth, 1958- (University of Toronto Press, 2016)
"First World Petro-Politics examines the vital yet understudied case of a first world petro-state facing related social, ecological, and economic crises in the context of recent critical work on fossil capitalism."--